Prevalence and risk factors associated with food insecurity among post-flood victims in Bera District, Pahang Malaysia / Nor Azizah Mohamed - Mohamed, Nor Azizah (2016)
Previous studies indicate the increment of food insecurity in Malaysia and it might be affect Malaysian nutritional and health status. This cross-sectional study determined the prevalence of food insecurity and examined the risk factors that contribute to the food insecure among the post flood victims in Bera district, Pahang Malaysia. Convenience sampling was applied and 210 households participated in this study. Household food security scales, chi-square and logistic regression were utilized to determined percentage of food insecure among flood victims and determined of factors associated with household food insecurity respectively. This study reported prevalence of food insecurity after flood at Bera district, Pahang Malaysia are 11.9% by using Household Food Insecurity Access Scale (HFIAS) while 34.9% by using Household Food Security Survey Module (HFSSM) tools. Logistic regression indicates the risk factors that associated with household food insecure among post flood victims are home damage, large household composition, and unaffordable food prices which 0.446, 1.18 and 5.94 times tend to food insecure respectively. Thus, this finding provide guidance on how to build more sustainable, resilient communities that immune to food security crisis over the long term and help government to plan proper policy regarding food security during flood. Keywords: Flood, Food insecurity, household, prevalence, Malaysia